Dioscin relieves diabetic nephropathy via suppressing oxidative stress and apoptosis, and improving mitochondrial quality and quantity control. Issue 6 (9th March 2022) - Zhong, Yujie; Liu, Jiayu; Sun, Dianjun; Guo, Tianmin; Yao, Yanpeng; Xia, Xiaodong; Shi, Chao; Peng, Xiaoli
Abstract : Oxidative stress, inflammation, apoptosis, mitophagy and mitochondrial fission/fusion contributed to the protective effect of Dioscin on diabetic nephropathy in rat. Abstract : Dioscin is a steroidal saponin isolated from various kinds of vegetables and herbs and possesses various biological activities. In this study, the protective effect of dioscin on diabetic nephropathy (DN) was explored. Dioscin and metformin (positive control) were administered orally to diabetic rats daily for 8 weeks. The biochemistry parameters, pancreas and kidney histological changes, oxidative stress, inflammation, apoptosis, autophagy, and mitochondrial quality and quantity control (mitophagy and mitochondrial fission/fusion) were measured. Our results showed that dioscin effectively reduced blood glucose, pancreatic injury, renal function markers and renal pathological changes in DN rat kidneys. Dioscin reduced O 2− and H2 O2 levels, decreased MDA levels, enhanced antioxidant enzyme (SOD, CAT) activities, and reduced inflammatory factor expressions. Moreover, NOX4 expression and the disorder of the mitochondrial respiratory chain were reversed by dioscin. Furthermore, apoptosis mediated by the mitochondria and ER stress was inhibited by dioscin through downregulating the expressions of Bax, CytC, Apaf-1, caspase 9, p-PERK, p-EIF2α, IRE1, p-IRE1, XBP1s, ATF4, p-CHOP and caspase 12. In addition, autophagy was enhanced by dioscin via an AMPK-mTOR pathway. Mitophagy and mitochondrial fission/fusion belong to the mitochondrial quality and quantity control process, which was improved by dioscin via regulating Parkin, PINK1, DRP1, p-DRP1 and MFN2 expressions. Collectively, these results suggested that dioscin protected against DN through inhibiting oxidative stress, inflammation, and apoptosis mediated by the mitochondria and ER stress. Autophagy and mitochondrial quality and quantity control (mitophagy and mitochondrial fission/fusion) were also improved by dioscin.